2021
DOI: 10.3389/fonc.2021.618839
|View full text |Cite
|
Sign up to set email alerts
|

IL-1β Promotes Vasculogenic Mimicry of Breast Cancer Cells Through p38/MAPK and PI3K/Akt Signaling Pathways

Abstract: Vasculogenic mimicry (VM), a micro vessel-like structure formed by the cancer cells, plays a pivotal role in cancer malignancy and progression. Interleukin-1 beta (IL-1β) is an active pro-inflammatory cytokine and elevated in many tumor types, including breast cancer. However, the effect of IL-1β on the VM of breast cancer has not been clearly elucidated. In this study, breast cancer cells (MCF-7 and MDA-MB-231) were used to study the effect of IL-1β on the changes that can promote VM. The evidence for VM stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…In patients with short survival time (< 5 years), the expression of JUN in breast cancer tissue is down-regulated and the risk of recurrence of breast cancer is increased (24). Furthermore, JUN mediates the functions of some important cytokines in breast cancer, such as IL-34, IL-33, and IL-1b (22,23,25). On the other hand, SIN3A is a transcriptional suppressor promoting osteolytic destruction in ERa-positive breast cancer (26).…”
Section: Discussionmentioning
confidence: 99%
“…In patients with short survival time (< 5 years), the expression of JUN in breast cancer tissue is down-regulated and the risk of recurrence of breast cancer is increased (24). Furthermore, JUN mediates the functions of some important cytokines in breast cancer, such as IL-34, IL-33, and IL-1b (22,23,25). On the other hand, SIN3A is a transcriptional suppressor promoting osteolytic destruction in ERa-positive breast cancer (26).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the TNBC MDA-MB-231 and HCC1937 cells readily formed tubular-like structures in Matrigel [ 36 , 37 ]. In comparison, the ERα-positive cell line MCF-7 has been reported to be incapable of forming VM in this matrix [ 36 ]; however, in the presence of some VM drivers such as interleukin 1β, MCF-7 cells formed microvessel-like intersections and cords [ 38 ]. Further studies are needed to corroborate the effects of VM-drivers upon tubular-like structure formation in ER-positive breast cancer cells.…”
Section: Relationship Between Vm and Tumor Phenotypementioning
confidence: 99%
“…On this subject, it is known that TNBC MDA-MB-231 cells express IL-8 as well as its receptors CXCR1/CXCR2, and notably, it has been shown that IL-8 uptake increases during VM formation and that IL-8/CXCR2 signaling is necessary for tube formation, a process that correlates with increased IL-8 levels [ 58 ]. In a similar manner but using a different signalization pathway, IL-1β has shown to stimulate VM formation by MCF-7 and MDA-MB-231 cells [ 38 ]. Indeed, when these cells were incubated in the presence of IL-1β, they readily formed tube-like structures in Matrigel and expressed VM biomarkers, including VE-Cadherin, VEGF receptor-1, MMP-9, and MMP-2.…”
Section: Drivers Of Vascular Mimicry In Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a study on more than 1,200 patients with BC showed a positive correlation between the increased VM positivity and larger tumor size, the propensity for metastasis, differentiation grade, and poor prognosis ( 14 ). Considering the characteristics of breast molecular subtypes and hormone-positive BC expression of VEGF ( 15 ), research has shown that cancer progression can be arrested or slowed down by targeting TGF-β1, MMP-2, and MMP-9 when irradiated by a proton beam ( 7 ). Additionally, the ERα-positive cell line MCF-7 has been reported to induce VM upon exposure to the VM mediator, interleukin 1β ( 7 ).…”
Section: Introductionmentioning
confidence: 99%